Enhancing visual and plastic education training: a blended learning and flipped classroom approach - Verónica Chust-Pérez; Rosa Pilar Esteve-Faubel; María Pilar Aparicio-Flores; José María Esteve-Faubel (Journal of New Approaches in Educational Research)
Abstract This article explores whether the implementation of the B-Learning (BL) and Flipped Classroom (FC) methodologies, using the ICT tool Edpuzzle, in the mandatory subject of Didactics of Plastic Expression in the Early Childhood Education teacher training programme leads to improvements in their education as future teachers. To address this investigation, two different pedagogical interventions were proposed: Unit 1 (U1), implementing BL, and Unit 2 (U2) through traditional lectures. For the analysis, a qualitative methodology using the focus group technique was employed. The results revealed high satisfaction among students regarding U1, implying that the use of ICT through the implementation of BL and FC methodologies has created a more dynamic and enriching educational environment, thereby enhancing their learning.